AVIATION CADETS’ PERCEPTION ON CONTENT-BASED LANGUAGE TRAINING AND SELF-ASSESSMENT - Setiyowati Setiyowati; Mashadi Said (Universitas Indraprasta PGRI, 2022)
This research is aimed to find out the effects of content-based language training on cadets speaking skills and to find out the effects of self-assessment on cadets speaking skills. The method employed in this research is survey. The research was done in semester six cadets at Indonesia Aviation Polytechnic in Curug and Makassar. Data was collected by administering an oral test (5 items), a content-based language training questionnaire (5 items), and a self-assessment questionnaire (30 items), in March until June 2021. The result of the research showed that (1) there are significant effects of Content-Based Language Training and Self-Assessment upon Cadets Speaking Skills. These have been proved by Sig score = 0.000 less than 0.05 and F count = 46.781 and the multiple contribution of Content-Based Language Training and Self-Assessment simultaneously gives 62.1% contribution on variable Cadets Speaking Skills; (2) there are significant effects of Content-Based Language Training upon Cadets Speaking Skills. These have been proved by Sig score = 0.000 less than 0.05 and t count = 7.226 and the partial contribution of Content-Based Language Training on Cadets Speaking Skills is 57.85%; (3) there are no effects of Self-Assessment on Cadets Speaking Skills. These have been proved by Sig score = 0.423 more than 0.05 and t count = 0.806 and the partial contribution of Self-Assessment on Cadets Speaking Skills is only 4.30%.